The Impact of Economic Recession on the Financial Support of State Functions during Crisis Situations - ARTEMCHUK, Mykyta; MARUKHLENKO, Oksana; SOKROVOLSKA, Nataliia; MAZUR, Hennadii; RIZNYK, Dmytro (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
The state faces significant challenges in fulfilling its functions during a recession, and crises only exacerbate the problems that arise. However, it is precisely during crises that adequate social security, defense, and other state functions are critically important for ensuring national and individual public interests. The purpose of the study was to analyze the impact of economic recession on the level of financial support for state functions during a crisis. The study used methods of statistical analysis, comparative analysis, analogy, abstraction, and generalization. As a result of the study, the revenues of the state budget of Ukraine and its financing were analyzed as the main sources of financial support for state functions. It was found that the share of tax revenues decreased from 85.37% in 2021 to 45.04% in 2023, which poses a threat to the state's ability to perform its functions. Significant budget financing amounts (31094 million USD in 2022 and 42479.15 million USD in 2023) positively influenced the country's defense capability but led to an increase in the state debt. Insufficient gold and foreign exchange reserves and the state debt reaching the GDP volume are the most negative trends. By analyzing international experience, it was determined that Ukraine should pay high attention to optimizing internal revenue sources, especially tax revenues, through fiscal incentives and ensuring tax discipline. It is also necessary to develop long-term strategies for repaying the state debt and international cooperation. The research results can be useful for government officials in the process of developing budget and tax policies.